1990
DOI: 10.1007/bf01806288
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptors and prognosis in primary breast cancer

Abstract: A retrospective study was performed on 109 human breast tumors stored in liquid nitrogen in order to assess the prognostic value of epidermal growth factor receptor (EGF-R) (median patient follow-up 5 years). A significant inverse relationship was observed between EGF-R and both estrogen (ER) and progesterone receptors (PR). Univariate analysis showed a trend towards a shorter metastasis-free survival both in the overall population and in node-negative patients with EGF-R positive tumors. Multivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Moreover, in the present study we did not observe a correlation of EGFR with steroid hormone receptor and this is in agreement with some other studies (Fitzpatrick et al, 1984;Peyrat et al, 1984;Bevilacqua et al, 1990) but in disagreement with the majority of authors who reported a significant inverse relationship between EGFR expression and ER-positivity (Koenders et al, 1991;Sainsbury et al, 1987;Lewis et al, 1990;Spyratos et al, 1990). There is also conflicting data in the literature regarding the relationship between EGFR and cell kinetics parameters in human breast carcinoma (Walker & Camplejohn, 1986;Gasparini et al, 1991).…”
Section: Monthssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in the present study we did not observe a correlation of EGFR with steroid hormone receptor and this is in agreement with some other studies (Fitzpatrick et al, 1984;Peyrat et al, 1984;Bevilacqua et al, 1990) but in disagreement with the majority of authors who reported a significant inverse relationship between EGFR expression and ER-positivity (Koenders et al, 1991;Sainsbury et al, 1987;Lewis et al, 1990;Spyratos et al, 1990). There is also conflicting data in the literature regarding the relationship between EGFR and cell kinetics parameters in human breast carcinoma (Walker & Camplejohn, 1986;Gasparini et al, 1991).…”
Section: Monthssupporting
confidence: 92%
“…Thus, in our experience, the overall picture is that EGFR status seems to be independent not only from the conventional pathologic parameters but also from some of the new (Foekens et al, 1989;Spyratos et al, 1990). In our series EGFR status is a significant prognostic factor for recurrence, but not for overall survival when evaluated by univariate analysis.…”
Section: Monthssupporting
confidence: 52%
“…We also report that SHBG inhibits the estradiol induction of EGF-R. EGF-R or HER1 is a member of the epidermal growth factor family of trans-membrane receptors [29] and it has been reported to be induced by estradiol [30] . Overexpression of EGF-R in breast cancer, that has been reported to occur in up to 14 % of tumors [31] , is considered a negative prognostic factor [32] , especially if it occurs together with over-expression of other genes such as c-myc [33] . Moreover, EGF-R is involved in a bidirectional cross-talk with estrogen receptors and the activation of the EGF-R-derived signaling pathway could amplify estradiol effect in breast cancer [34] .…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is located on 7q12 and codes for the EGFR, a transmembranous receptor protein with kinase activity. EGFR was found amplified in 0 to 14% of breast cancers (13,32). The role of EGFR has regained interest in breast cancer because EGFR interacts with HER2, a therapeutic target protein and because of the availability of drugs that directly target EGFR.…”
Section: Introductionmentioning
confidence: 99%